Do Questions Get Infants Talking? Infant Vocal Responses to Questions and Declaratives in Maternal Speech. Issue 3 (18th May 2016) - Reimchen, Melissa; Soderstrom, Melanie
Abstract : Maternal questions play a crucial role in early language acquisition by virtue of their special grammatical, prosodic and lexical forms, and their abundance in the input. Infants are able to discriminate questions from other sentence types and produce rising intonations in their own requests. This study examined whether caregiver questions were related to the quantity of infant vocalizations. Thirty‐six infants aged 10 and 14 months participated in a laboratory play session with their mothers. In separate blocks, mothers were instructed to ask questions and to refrain from asking questions. Both block‐level and utterance‐level analyses found no evidence that maternal questions affected the amount of infant‐response vocalizations. Mothers of 14‐month‐olds (but not 10‐month‐olds) tended to repeat questions. Copyright © 2016 John Wiley & Sons, Ltd.